Allelic Variation and Transcriptional Isoforms of Wheat TaMYC1 Gene Regulating Anthocyanin Synthesis in Pericarp - Zong, Yuan; Xi, Xinyuan; Li, Shiming; Chen, Wenjie; Zhang, Bo; Liu, Dengcai; Liu, Baolong; Wang, Daowen; Zhang, Huaigang (Frontiers in Plant Science, 2017)
Recently the TaMYC1 gene encoding bHLH transcription factor has been isolated from the bread wheat (Triticum aestivum L.) genome and shown to co-locate with the Pp3 gene conferring purple pericarp color. As a functional evidence of TaMYC1 and Pp3 being the same, higher transcriptional activity of the TaMYC1 gene in colored pericarp compared to uncolored one has been demonstrated. In the current study, we present additional strong evidences of TaMYC1 to be a synonym of Pp3. Furthermore, we have found differences between dominant and recessive Pp3(TaMyc1) alleles. Light enhancement of TaMYC1 transcription was paralleled with increased AP accumulation only in purple-grain wheat. Coexpression of TaMYC1 and the maize MYB TF gene ZmC1 induced AP accumulation in the coleoptile of white-grain wheat. Suppression of TaMYC1 significantly reduced AP content in purple grains. Two distinct TaMYC1 alleles (TaMYC1p and TaMYC1w) were isolated from purple- and white-grained wheat, respectively. A unique, compound cis-acting regulatory element had six copies in the promoter of TaMYC1p, but was present only once in TaMYC1w. Analysis of recombinant inbred lines showed that TaMYC1p was necessary but not sufficient for AP accumulation in the pericarp tissues. Examination of larger sets of germplasm lines indicated that the evolution of purple pericarp in tetraploid wheat was accompanied by the presence of TaMYC1p. Our findings may promote more systematic basic and applied studies of anthocyanins in common wheat and related Triticeae crops.